Determinants of subjective well-being: perspectives of Malay Muslims / Nor Hafizah Mohamed Harith and Hazizan Md. Noon - Mohamed Harith, Nor Hafizah; Md. Noon, Hazizan (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
In modern and industrialized societies, the level of quality of life or life style is measured objectively by economic parameters such as income inequality rate, literacy rate and life expectancy. Many economists believe that money buys happiness, and so, income is the sole measure of well-being. Economists typically equate economic development with per capita income or product, and they usually measure inequality and poverty in terms of real income or consumptions. However, in the early 1970s, Easterlin found that happiness, from the perspective of SWB, does not seem to rise systematically with income. Indeed, this finding seems to be in contradiction with the basic assumption of many economists. Therefore, it is important to provide an insight into the issue on how significant the meaning of happiness or life satisfaction among people. Thus, the main objective of this study is to determine the meaning of well-being among the Malay Muslim respondents. The study adopted a qualitative approach that involved 16 people who worked in University MARA Technology Shah Alam. Data were analyzed using thematic analysis and NVivo 9 was utilized as data management software. Results of the study shows that the themes were centered on 1) the need of spiritual need 2) the economic satisfaction needs & 3) the social needs. The study also revealed significant impacts to policy implications in Malaysia.